Implementation of the Discovery Learning Model in Natural and Social Science Lessons (IPAS) in Madrasah Ibtidaiyah: Implementasi Model Discovery Learning pada Pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di Madrasah Ibtidaiyah - Roso Murti (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2023)
This study aims to get a real picture of the implementation of the discovery learning model in the learning of Natural and Social Sciences (IPAS) from the steps and efforts made to overcome obstacles in the implementation of the discovery learning model. This study is descriptive with a qualitative approach. The research subjects were fourth grade teachers and fourth grade students of Madrasah Ibtidaiyah Negeri 1 Temanggung. Data collection techniques include observation, interviews and documentation. The data analysis uses a descriptive analysis model consisting of data collection, organization, management, verification, interpretation, and conclusions. Then the data validity technique uses method and source triangulation techniques. Based on the results of the study, it was concluded that (1) The implementation of the discovery learning model in Natural and Social Science lessons at Madrasah Ibtidaiyah Negeri 1 Temanggung went through six stages, namely, stimulation, problem identification, data collection, data processing, proof and conclusion drawing. (2) In the process, teachers experience several obstacles, including taking up a lot of teacher time and work. Teachers felt that they did not detect the problem and there were misunderstandings between teachers and students. Not all students are capable of discovery. For students who are less clever, they will have difficulty thinking to reveal the relationship between concepts. However, teachers and students try to overcome these obstacles so that the learning objectives can be achieved well. Abstrak Penelitian ini bertujuan untuk mendapatkan gambaran nyata mengenai pelaksanaan model discovery learning pada pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) dari langkah dan upaya yang dilakukan untuk mengatasi hambatan dan kendala dalam implementasi model discovery learning. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Subyek penelitian adalah guru kelas IV dan siswa kelas IV Madrasah Ibtidaiyah Negeri 1 Temanggung. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Analisis data menggunakan model analisis deskriptif yang terdiri dari pengumpulan data, pengorganisasian, pengelolaan, verifikasi, penafsiran, dan kesimpulan. Keabsahan data menggunakan teknik triangulasi metode dan sumber. Berdasarkan hasil penelitian, diperoleh kesimpulan bahwa (1) Pelaksanaan model discovery learning pada pelajaran Ilmu Pengetahuan Alam dan Sosial di Madrasah Ibtidaiyah Negeri 1 Temanggung melalui enam tahap yaitu: stimulasi, identifikasi masalah, pengumpulan data, pengolahan data, pembuktian dan penarikan kesimpulan. (2) Dalam prosesnya, guru mengalami beberapa kendala, antara lain: menyita banyak waktu dan pekerjaan guru, guru merasa kurang mendeteksi masalah, terjadi kesalahpahaman antara guru dan siswa, tidak semua siswa mampu melakukan penemuan. Bagi siswa yang kurang pandai mereka akan mengalami kesulitan dalam berpikir untuk mengungkapkan hubungan antar konsep. Namun, guru dan siswa berusaha untuk mengatasi kendala tersebut agar tujuan pembelajaran dapat tercapai dengan baik.